2021
DOI: 10.1038/s41419-020-03365-1
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis is active and contributes to intestinal injury in a piglet model with lipopolysaccharide challenge

Abstract: Necroptosis, a newly discovered form of programmed cell death that combines the features of apoptosis and necrosis, is important in various physiological and pathological disorders. However, the role of necroptosis on intestinal injury during sepsis has been rarely evaluated. This study aimed to investigate the presence of necroptosis in intestinal injury, and its contribution to intestinal injury in a piglet model challenged with Escherichia coli lipopolysaccharide (LPS). Firstly, a typical cell necrotic phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 44 publications
3
40
0
Order By: Relevance
“…Necroptosis induction is the activation of serine/threonine kinase RIPK1 via a cascade of signaling pathways involving the tumor necrosis factor (TNF) receptor superfamily, T cell receptors, interferon receptors, Toll-like receptors (TLRs), cellular metabolic and genotoxic stresses, or various anticancer agents that induce necroptosis [ 1 , 12 , 30 , 31 ]. Additionally, necrostatin-1 (Nec-1), a particular necroptosis inhibitor, inhibits necroptosis as demonstrated by decreased necrotic ultrastructural changes and lower expression levels of RIPK1, RIPK3, phosphorylated MLKL, PGAM5, DRP1, and cytoplasmic HMGB1 [ 32 , 33 ].…”
Section: Necroptosismentioning
confidence: 99%
“…Necroptosis induction is the activation of serine/threonine kinase RIPK1 via a cascade of signaling pathways involving the tumor necrosis factor (TNF) receptor superfamily, T cell receptors, interferon receptors, Toll-like receptors (TLRs), cellular metabolic and genotoxic stresses, or various anticancer agents that induce necroptosis [ 1 , 12 , 30 , 31 ]. Additionally, necrostatin-1 (Nec-1), a particular necroptosis inhibitor, inhibits necroptosis as demonstrated by decreased necrotic ultrastructural changes and lower expression levels of RIPK1, RIPK3, phosphorylated MLKL, PGAM5, DRP1, and cytoplasmic HMGB1 [ 32 , 33 ].…”
Section: Necroptosismentioning
confidence: 99%
“… 115 Necroptosis acts as a trigger of inflammation in many diseases. 116 , 117 Increased necroptosis is also implicated in sepsis through promoting the release or activation of inflammatory effectors, such as HMGB1, 118 , 119 , 120 TNF-related apoptosis-inducing ligand, 121 and gasdermin D (GSDMD). 122 STING1 signals can trigger necroptosis and promote inflammation by initiating MLKL expression or inducing MLKL phosphorylation.…”
Section: Sting1 and Cell Death In Sepsismentioning
confidence: 99%
“…Increasing evidence revealed that the disruption of microbiome could predispose to sepsis and exert negative influences on sepsis outcomes ( 30 , 128 ). On the other hand, sepsis is closely related to disruption of the intestinal barrier ( 129 ), and improving intestinal barrier function might be a new focus for further investigations and clinical treatment. Intestinal tract is another important target organs in the development of sepsis, with the capacity of inducing multiple organ injuries eventually.…”
Section: Lncrnas In Gastrointestinal System During Sepsismentioning
confidence: 99%